ANALYZING THE EFFECTS OF USING BOTH FOLDABLE AND STANDARD CONTAINERS IN OCEAN TRANSPORTATION - Myung, Young-soo; Moon, Ilkyeong; Lee, Jongheon; Lee, Kyungsik (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
We analyze the effects of foldable containers using a newly developed multi-port and multi-period container planning model. The proposed model is a large-scale optimization problem, for which we develop an efficient heuristic algorithm to get near-optimal solutions within a reasonable time. Our model improves existing models by including practical assumptions on the supply of empty containers at each port in each period. Through intensive computational experiments, we analyze the effect of the imbalance in demand and the decreases in the purchasing cost and the handling cost of foldable containers on the potential economic benefits of deploying foldable containers in ocean transportation